2008
DOI: 10.1007/s11581-008-0244-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mixed cations in synergizing the performance characteristics of PVA-based polymer electrolytes for novel category Zn/AgO polymer batteries—a preliminary study

Abstract: Thin films of polymer electrolytes comprising of PVA and KOH (A) with and without the addition of zinc salts, viz., zinc acetate (B) and zinc triflate (C) as mixed cations were prepared via. solution casting method. The thermal stability and ionic conductivity of PVA-KOH solid polymer electrolyte (A) were improved by the partial substitution of KOH with zinc salts. Among the two salts, zinc triflate was found to improve both the physical as well as electrochemical properties of the PVA-KOH films more significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…After 100 chargedischarge cycles, the Zn/Ni battery with this electrolyte exhibited 55% capacity retention. Zn(CH 3 COO) 2 and Zn (CF 3 SO 3 ) 2 were tested as a salt mixture in the PVA/KOH system and synergized the thermal stability and ion conductivity of the blended electrolyte 92 . For these two SPEs, that with Zn(CF 3 SO 3 ) 2 was found to improve the dimensional stability of PVA/KOH films more distinctly than that with Zn(CH 3 COO) 2 .…”
Section: Pva and Its Derivativesmentioning
confidence: 99%
“…After 100 chargedischarge cycles, the Zn/Ni battery with this electrolyte exhibited 55% capacity retention. Zn(CH 3 COO) 2 and Zn (CF 3 SO 3 ) 2 were tested as a salt mixture in the PVA/KOH system and synergized the thermal stability and ion conductivity of the blended electrolyte 92 . For these two SPEs, that with Zn(CF 3 SO 3 ) 2 was found to improve the dimensional stability of PVA/KOH films more distinctly than that with Zn(CH 3 COO) 2 .…”
Section: Pva and Its Derivativesmentioning
confidence: 99%
“…33 They reported that the crystalline peak intensity decreases in the XRD pattern of PVA indicate the increased amorphous nature with the addition of dopants. 34 Therefore, the diminished crystalline peak intensity at 2θ = 11.84°i n the XRD pattern of PVA/ZnAc SPEs for 20 wt% of ZnAc loading is attributed to the presence of amorphous rich phase. 35 Further, it is observed that the variation of crystallite size and crystallinity in PVA/ZnAc SPEs is in accordance with the free volumes of the system.…”
Section: Resultsmentioning
confidence: 96%
“…Assembling with Zn and MnO 2 electrodes on a polymer host poly(3,4‐ethylene dioxythiophene) (PEDOT) as shown in Figure a, the fabricated Zn/MnO 2 @PEDOT flexible battery presents a high capacity of 282.4 mAh g −1 , 77.7% of its initial capacity and nearly 100% Coulombic efficiency after 300 cycles (Figure 8b). Mohamad et al [ 92 ] and Vatsalarani et al [ 93 ] have also developed PVA‐based SPEs for alkaline ZIBs, which exhibited a high ionic conductivity of 8.7 × 10 −3 S cm −1 , where KOH and Zn(CH 3 COO) 2 are dissolved into the complex. Assembling within a Zn/AgO battery configuration, a minimum specific capacity loss of ≈3% has been observed over 20 cycles.…”
Section: Hydrogel Polymer Electrolytementioning
confidence: 99%